The Influence of Organizational Citizenship Behavior on the Kindergarten Teacher's Performance in Cimahi, West Java, Indonesia - Ramadhan, Nabilah; Solihin, Ismail; Silviani Marinda, Vina (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to find out how much the influence of organizational citizenship behavior (OCB) is driving the emergence of kindergarten teacher’s performance in Cimahi. The influence is expected to create increased productivity in adapting to the conditions of organizational development and a high level of engagement from the teacher to the organization. The type of research used is a combination of descriptive methods and correlation methods by taking a sample of 110 kindergarten teachers in Cimahi. Data analysis used in hypothesis testing is simple linear regression analysis. From the results of the study, it can be concluded that the level of OCB that occurs in kindergarten teachers is high with a percentage of 81.4%, while the application of teacher’s performance is also high with a percentage of 82.2%. The results show that OCB has a positive and significant effect on teacher’s performance, with an effect of 50.7%. While the remaining influence of 49.3% is caused by other variables outside the research model.